Three-Dimensional Morphology of Temporomandibular Joint in Patients with Class I, Class II and Class III Malocclusion: A CBCT Study (Journal of Pharmaceutical Negative Results, 2022)
Background: Varying types of malocclusions may have an effect on the morphology and position of the condyle in the glenoid fossa.Aim: This retrospective study aims to evaluate and compare the three-dimensional position and morphology of the condyle in the glenoid fossa in Angle’s Class I, Class II division I, Class II division II and Class III malocclusions using cone-beam computed tomography panoramic reconstructions.Material and Method: Pre-treatment CBCT scans of 40 subjects (17-30 years) with 10 subjects in each of the study groups as per Angle’s malocclusion were obtained. The CBCT images of all subjects were evaluated and compared following parameters, i.e., differences in anterior joint space, posterior joint space, superior joint space, anteroposterior and mediolateral width of the condyle, condylar height, and the vertical distance of the geometric center of the condyle from the mid-sagittal plane.Result: Statistical analysis revealed all parameters were statistically similar for all the malocclusion groups except the anterior and the superior joint space. The latter two parameters were significantly smaller in subjects with class III malocclusion compared to class I (p <0.05).Conclusion: The Anterior joint space and the Superior joint space were statistically significantly larger in the Class I malocclusion group when compared with the Class III malocclusion group. This implies that condyles were more superiorly and anteriorly placed in subjects with class III malocclusion. These differences could be considered during the diagnosis temporomandibular disorders and orthodontic treatment.